2019
DOI: 10.1002/humu.23862
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of genotype‐phenotype associations in Bardet‐Biedl syndrome uncovers differences among causative genes

Abstract: Bardet‐Biedl syndrome (BBS) is a recessive genetic disease causing multiple organ anomalies. Most patients carry mutations in genes encoding for the subunits of the BBSome, an octameric ciliary transport complex, or accessory proteins involved in the BBSome assembly or function. BBS proteins have been extensively studied using in vitro, cellular, and animal models. However, the molecular functions of particular BBS proteins and the etiology of the BBS symptoms are still largely elusive. In this study, we appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(144 citation statements)
references
References 133 publications
(261 reference statements)
12
121
0
Order By: Relevance
“…A recent metanalysis has assembled the data of 85 of the most relevant published articles describing both the genotype and the phenotype of patients with BBS, which has led to the creation of the largest cohort, accounting for 899 individuals. 33 The study concluded that: 1) renal anomalies have a higher incidence in patients with BBS2 , BBS7 , and BBS9 (the core of the BBSome) mutations compared with other BBSome components ( BBS1 , BBS4 , and BBS8/TTC8 ); 2) patients with mutations in BBS1 have a lower incidence of renal anomalies than the other most common BBS genes, namely BBS2 and BBS10 , and that this effect is independent on the high incidence of the M390R variant; and 3) patients with BBS3/ARL6 mutations have a low rate of kidney disease and cognitive impairment. The study also confirmed previous analyses suggesting that truncating mutations are significantly correlated with higher disease severity than missense mutations.…”
Section: Genetics Of Bbsmentioning
confidence: 99%
“…A recent metanalysis has assembled the data of 85 of the most relevant published articles describing both the genotype and the phenotype of patients with BBS, which has led to the creation of the largest cohort, accounting for 899 individuals. 33 The study concluded that: 1) renal anomalies have a higher incidence in patients with BBS2 , BBS7 , and BBS9 (the core of the BBSome) mutations compared with other BBSome components ( BBS1 , BBS4 , and BBS8/TTC8 ); 2) patients with mutations in BBS1 have a lower incidence of renal anomalies than the other most common BBS genes, namely BBS2 and BBS10 , and that this effect is independent on the high incidence of the M390R variant; and 3) patients with BBS3/ARL6 mutations have a low rate of kidney disease and cognitive impairment. The study also confirmed previous analyses suggesting that truncating mutations are significantly correlated with higher disease severity than missense mutations.…”
Section: Genetics Of Bbsmentioning
confidence: 99%
“…[2], it is probable that the chaperonin complex assists any of the initial steps of the BBSome formation as suggested previously[21] rather than the BBS1-dependent translocation into the ciliary base. However, this should be experimentally addressed in further studies.Overall, our study reveals that the BBSome formation is a sequential process with spatially compartmentalized steps.…”
mentioning
confidence: 57%
“…Mutations in any of the BBSome subunits can cause the BBS, suggesting that every subunit is essential for the complete BBSome function [2]. The structure of the BBSome was a longstanding enigma until recently, because the indirect approaches such as the yeast two-hybrid system [16], co-precipitation [17], co-expression of the individual subunits followed by lowresolution cryo-electron microscopy (EM) [18], and structural analysis of individual BBSome subunits [19,20] provided only a very limited insight into the overall BBSome structure.…”
Section: Introductionmentioning
confidence: 99%
“…The one exception here is the renal phenotype. A recent meta‐analysis study in the Czech Republic found that the core BBSome subunits BBS2, 7 and 9 manifest as more critical in the kidney [Niederlova et al., ]. Similarly, the risk factor for severe renal disease were found to vary between patients harbouring BBS1, 2, 9, 10 or 12 mutations in a detailed study with 350 BBS patients in the UK [Forsythe et al., ].…”
Section: Discussionmentioning
confidence: 99%